2020
DOI: 10.1029/2020ja027798
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Electron Flux Oscillations as Observed by MagEIS in Response to Broadband ULF Waves

Abstract: Coherent electron flux oscillations of hundreds of keV are often observed by the Van Allen Probes in the magnetosphere during quiet times in association with ultralow frequency (ULF) waves. They are observed in the form of periodic flux fluctuations, with a drift frequency that is energy dependent, but are not associated with drift echoes following storm‐ or substorm‐related energetic particle injections. Instead, they are associated with the resonant interaction of electrons with ULF waves and are an indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Our result indicates that the excitation of shock‐related ULF waves is more likely determined by internal local condition in the magnetosphere. This study may be helpful for understanding the effect of shock on Earth's magnetosphere and quantification of radiation belt electron, as ULF waves can greatly affect magnetospheric electron population (e.g., Hao et al, 2014; Ren et al, 2017; Sarris et al, 2017, 2020; Zhou et al, 2016; Zong et al, 2009). Further observations and simulation on how shock‐induced ULF wave distributes in realistic magnetosphere are in need to be carried out in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Our result indicates that the excitation of shock‐related ULF waves is more likely determined by internal local condition in the magnetosphere. This study may be helpful for understanding the effect of shock on Earth's magnetosphere and quantification of radiation belt electron, as ULF waves can greatly affect magnetospheric electron population (e.g., Hao et al, 2014; Ren et al, 2017; Sarris et al, 2017, 2020; Zhou et al, 2016; Zong et al, 2009). Further observations and simulation on how shock‐induced ULF wave distributes in realistic magnetosphere are in need to be carried out in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic radial transport, more commonly referred to as radial diffusion, results from the interaction of particles with a spectrum of waves with frequencies commensurate with the drift frequency of the particles (e.g. Elkington et al 2003), although repetitive advective processes such as substorms may lead to the diffusive radial transport of particles over longenough timescales (Chen et al 1992;Sarris et al 2017Sarris et al , 2020. Radial diffusion will tend to move particles in aggregate in the direction opposite the prevailing gradients of the local phase space density.…”
Section: Drift Effectsmentioning
confidence: 99%
“…Instead, they can be linked to the resonant interaction of electrons with ULF waves and, as discussed in Sarris et al. (2020), they could be used as an indicator of electron radial diffusion. It was demonstrated that critical in the observations of flux oscillations is the width of electron detector energy channels, with narrower energy channels enabling the detection of flux oscillations of smaller amplitude.…”
Section: Introductionmentioning
confidence: 99%